Caracterização de vinhos produzidos na região central do Rio Grande do Sul - Costa, Eduarda Lasch (2022)
The location of cultivation influences on the oenological and sensory characteristics of wines and currently there are few studies on wines produced in the Central Region of RS. This study aimed to carry out the physical-chemical, phenolic and mineral characterization of commercial wines produced in this region and to assess if there are correlations between the characterization and the climatic conditions of the region. The physicochemical characteristics (alcohol content, total reducing sugars, total and volatile acidity, pH, hue and color intensity), total phenolic compounds and total anthocyanins of 25 commercial wines were evaluated. The wines were produced in the Central Region of RS in the 2018, 2019 and 2020 harvests. The content of minerals (nitrogen, phosphorus, potassium, calcium, magnesium, manganese, copper, zinc and iron) were also determined. Data referring to hourly air temperature, hourly precipitation and hourly solar radiation from December to March of 2017, 2018, 2019 and 2020 were used. The results were subjected to analysis of variance followed by Student's T test or Tukey's test (p<0.05) and Pearson's correlation. All wines were classified as fine dry wines, with a low content of total reducing sugars, between 0.14 and 1.04 g/L, and an alcohol content between 11.3 and 13.9%. In addition, for pH, total and volatile acidity, all wines were within the parameters of Brazilian legislation, with the exception of two wines from the 2020 harvest, obtained from the same winery, which presented volatile acidity above the allowed. The wines showed high color intensity and hue was lower in the wines from 2020 harvest, showing the evolution of the color of the wine. The content of phenolic compounds and anthocyanins was quite heterogeneous, influenced by cultivars and season. Regarding the mineral content, the wines from the Central Region showed intermediate levels of nitrogen and manganese; high levels of phosphorus, potassium and magnesium; and low levels of calcium and zinc. The iron and copper minerals presented very low contents, the latter being within the parameters required by the Brazilian Legislation for inorganic contaminants in wine. Correlations were observed between the physicochemical and anthocyanin characteristics of Malbec and Merlot 1 wines and the climatic variables. In general, the strength of the correlations obtained was different for the two cultivars. In addition, the climatic variables of the months of February and March were the ones that were more correlated with the physicochemical and phenolic characteristics of the wines. Therefore, both the cultivar and/or cut factor, as well as the harvest factor, had an effect on the physicochemical and mineral characteristics of commercial wines produced in the Central Region of Rio Grande do Sul. Also, despite strong correlations being observed, it was not possible to establish causal relationships between the variables.